Scaling opportunity crops in Africa through a multi-stakeholder platform: Aligning with Agenda 2063, Post-Malabo commitments and global policy frameworks - Otieno, Gloria; Grazioli, Francesca; Mendonce, Sharon; Fadda, Carlo; Rokka, Sussana; Boari, Francesca; El Bilali, Hamid (Bioversity International, 2025)
This policy brief presents the African Opportunity Crops Working Group—a multi-stakeholder platform established under the African Union’s African Seed and Biotechnology Platform (ASBP). Led by the Alliance of Bioversity International and CIAT, with the Forum for Agricultural Research in Africa (FARA) and the World Vegetable Center as co-leads, the Working Group serves as a coordination mechanism to scale up and mainstream opportunity crops across Africa. It does this in alignment with key continental frameworks such as the Post-Malabo Declaration and the African Union’s Agenda 2063. Through a coordinated and inclusive approach, the Working Group aims to foster innovation, policy coherence, and investment to strengthen food and nutrition security, enhance climate resilience, and advance Africa’s long-term socio-economic transformation. Learn more about the Working Group here: https://hdl.handle.net/10568/176847